AKAL MENURUT CENDEKIAWAN MUSLIM KLASIK DAN KONTEMPORER - Lubis, Sakban (Jurnal Ilmiah Al-Hadi, 2018)
The word al-‘aql etimologically has various meanings, they are the persistence of something (al-tatsabbut fi al-umur), restraint and trying to hold back (al-imsāk wa al-imtisāk), or preventing (al-man'u) as in the saying: "I prevent the camel from running away ". This paper will reveal the nature of ‘aql according to classical, modern and contemporary Muslim scholars. From this, it can be concluded that the reason for Muslim scholars both classical and contemporary has a high position in religion. The only difference lies in the emphasis on meaning only in accordance with their respective scientific backgrounds. In this context, reason is not against religion, and vice versa. Like a person who walks in darkness, reason is an eye while religion functions as an illumination. Both are two things that cannot be separated in judging something.